Cassava mosaic disease pandemic mitigation in East Africa; a systemwide whitefly IPM afflliated project: third quarterly technical report, phase 3 April-June 2001 - International Institute of Tropical Agriculture (2001)
A survey in which 142 farmers fields were visited was conducted in Tanzania during this quarter of the project. Of the II districts covered in the survey, 4 districts showed high CMD incidence and severity. One of these districts, Geita, was widely affected by. High incidence of severe CMD for the first time. Leaf and whitefly samples were also picked during the survey. In Uganda, ratooning was done, producing over 600 bags of planting material that was distributed to more than 1,500 beneficiaries in the districts of Rakai and Masaka. A total of 917 and 691 bags of SS4 and Migyera respectively were cut and distributed to limners, limner groups, NGOs and CBOs in Kenya. Additionally, at secondary sites, 21 and 15 ha in Western and Nyanza Provinces respectively were established. In Tanzania, 24,625 sterns of planting material were given to FFS and LPMIN farmer groups. At the Open Quarantine facility, evaluation of the 400 EARRNET derived clones continued during this quarter. Evaluation of tissue culture material continued at the three sites of Gera, Maruku and Bushasha. A nursery was also established using seeds collected from Open Quarantine. At the Open Quarantine facility in Kenya, 563 clones were planted as base stock material. 14 clones are also under multiplication in order to meet the demand for planting material. 175 clones have been planted in performance evaluation trials and a further 32 in and advanced yield trial in Migoi, near to the Tanzania border. Harvesting of evaluation trials at A1upe, Kakamega and Mbita Point was done during this quarter of the project. The o-arm trial at Matungu, Butere-Mmnias district was harvested. Farmers participated in the evaluation and selected varieties basing on their own criteria. Clone Unknown 3 was ranked best at two of the sites. Training organized by the Provincial Crops Officer for extension workers, farmers, COOS and NGOs was conducted in five districts of Western Province. 435 people were trained. Training in Nyanza province will be done in the next quarter of the project. A combined team of liT AlNARO and CEDO together with the farmers conducted a final evaluation of the material at the TTCs in Uganda. The material was harvested and farmers evaluated the different clones basing on their own criteria. The sites were replanted and excess material distributed to the farmers. Varieties 92100057, 92100067, TME 14 and 95/00087 were most highly ranked by limners. An agro-economist from IlTA-Benin, Ousmane Coulibaly, visited Uganda and Kenya to irritiate impact assessment of the project. A survey protocol has been developed and its implementation has been scheduled for August. There are also plans to hold steering committee meetings in Kenya and Tanzania and a Stakeholders meeting in Bukoba Tanzania during the next quarter of the project.